Analysis Quality of Employment Information Systems Using Webqual 4.0 and Importance Performance Analysis Method - I Gede, Bagus Premana Putra; Made, Sudarma; Nyoman, Gunantara (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2024)
Information system quality analysis is an aspect that information system managers must pay attention to, especially to meet user needs, increase comfort, and increase user productivity. SISNAKER, as the main information system used by the Department of Manpower and Energy and Mineral Resources of Bali Province to support services to the community digitally, also requires a quality analysis process to ensure user comfort when interacting with SISNAKER. This research aims to measure the quality of the employment information system, often called SISNAKER belonging Department of Manpower and Energy and Mineral Resources of Bali Province based on user perceptions and provide recommendations to improve the system quality. SISNAKER quality is measured using a questionnaire based on domains of the WebQual 4.0 method especially, usability, information quality, and interaction quality parameters. Mapping recommendations to improve SISNAKER quality is made based on four priority quadrants of the Importance Performance Analysis (IPA) method. The sampling of research was based on a proportionate stratified random sampling technique, involving a total of 98 respondents. The results of the research show that the gap between performance and user expectations is 0.02, which means that system performance is in line with user expectations. Improvement is found in information quality and interaction quality parameters, with -0.02 gap, so it still needs improvement.